Firm dynamics in developing countries: a single policy for all regions? - Calá, Carla Daniela (2015)
We analyse the determinants of firm dynamics in developing countries using Argentina as an illustrative case. We explain firm entry and exit at the regional level, distinguishing three groups of manufacturing activities: low, medium and high tech. We find that both region- and sector- specific determinants explain firm dynamics, but the impact is not homogeneous across the sectors considered. In particular, for low tech industries, there is a need for explanatory variables that proxy for the specificities of developing economies (e.g., poverty, informal economy and idle capacity). We also find evidence of a core-periphery pattern according to which agglomeration economies and previous entries and exits have different effects in core and peripheral regions. These results are relevant for policy makers in developing countries, who should take into account not only the specificities of such economies, but also the regional heterogeneity both in terms of the level of development and industrial composition within the country.